上顎洞を占拠した上顎骨粘液線維腫の1例 - 碇, 竜也; 中村, 誠司; 川野, 真太郎; 清島, 保; 緒方, 謙一; 松村, 万由 (日本口腔外科学会雑誌, 2020)
Myxofibroma of the jaw is a rare benign mesenchymal-related tumor. This tumor has the ability to deeply invade into bone trabeculae, and the recurrence rate is thus high. Here, we present a case of myxofibroma of the maxilla occupying the maxillary sinus. The patient was a 51-year-old woman with painless swelling of the right buccal region. CT findings revealed a well-defined and multilocular tumor mass in the maxillary sinus. The nasal cavity on the right was remarkably compressed by the tumor mass. The pathological diagnosis of the biopsy specimen was myxoma. Under general anesthesia, partial maxillectomy and skin grafting were performed. The pathological findings showed proliferation of stellate, spindleshaped, and round cells with myxoid and fibrous changes in the bone tissue. The pathological diagnosis was finally myxofibroma. Follow-up for 3 years after tumor resection indicated a good prognosis with no sign of recurrence.